Long‐term survival benefit of upfront chemotherapy in patients with newly diagnosed borderline resectable pancreatic cancer. (21st June 2017) - Shrestha, Bikram; Sun, Yifei; Faisal, Farzana; Kim, Victoria; Soares, Kevin; Blair, Alex; Herman, Joseph M.; Narang, Amol; Dholakia, Avani S.; Rosati, Lauren; Hacker‐Prietz, Amy; Chen, Linda; et al.
Abstract: The use of neoadjuvant chemotherapy or radiation for borderline resectable pancreatic adenocarcinoma (BL‐PDAC) is increasing. However, the impact of neoadjuvant chemotherapy and radiation therapy on the outcome of BL‐PDAC remains to be elucidated. We performed a retrospective analysis of 93 consecutive patients who were diagnosed with BL‐PDAC and primarily followed at Johns Hopkins Hospital between February 2007 and December 2012. Among 93 patients, 62% received upfront neoadjuvant chemotherapy followed by chemoradiation, whereas 20% received neoadjuvant chemoradiation alone and 15% neoadjuvant chemotherapy alone. Resectability following all neoadjuvant therapy was 44%. Patients who underwent resection with a curative intent had a median overall survival (mOS) of 25.8 months, whereas those who did not undergo surgery had a mOS of 11.9 months. However, resectability and overall survival were not significantly different between the three types of neoadjuvant therapy. Nevertheless, 22% (95% CI, 0.13–0.36) of the 58 patients who received upfront chemotherapy followed by chemoradiation remained alive for a minimum of 48 months compared to none of the 19 patients who received upfront chemoradiation. Among patients who underwent curative surgical resection, 32% (95% CI, 0.19–0.55) of those who received upfront chemotherapy remained disease free at least 48 months following surgical resection, whereas none of the eight patients who received upfront chemoradiation remained disease free beyond 24 months following surgical resection. Neoadjuvant therapy with upfront chemotherapy may result in long‐term survival in a subpopulation of patients with BL‐PDAC. Abstract : This is a retrospective, intention‐to‐treat analysis of consecutive patients who were diagnosed with borderline resectable pancreatic cancer and primarily followed at the Johns Hopkins Hospital. The results from this study highlight the importance of upfront systemic therapy in the management of borderline resectable pancreatic cancer.